THE DEVELOPMENT OF DURABLE ASPHALT PAVEMENT USING MODIFIED POLYMERS AND RESOL AS REINFORCING MATERIALS - Al-Essa, Abdul Razzakh; Mutar, Mohammed; Hussein, Ammar (Iraqi Journal of Science, 2024)
Asphalt is predominantly used to construct pavements for roads, highways, and airports. Both asphalt binder and asphalt – aggregate mixture show temperature and time dependent behavior. Rutting or permanent deformation is the leading cause of pavement deterioration in temperature and warm climatic regions of the world and low – temperature cracking is a common problem in cold regions. As the highway pavement infrastructure has aged and deteriorated, more pavements are in need of maintenance, rehabilitation, and reconstruction. This is traditionally done by placing hot mix asphalt overlay.Four contents of crumb rubber, waste plastic, polyvinyl alcohol, and resol are used. These are (2.5, 5.5, 8.0, 10.5)% by weight of aggregate, three contents of crumb rubber, waste plastic, polyvinyl alcohol, and resol are used as additives to asphalt cement represent about 1.3% from the percentage of asphalt cement. It was found that the addition of crumb rubber, waste plastic, polyvinyl alcohol, and resol increased the Marshall stability retained strength, and air voids.Resol and crumb rubber gave rise higher values of Marshall stability than waste plastic and polyvinyl alcohol. The study also allowed for the identification of many important engineering concerns which must be addressed in future, and more extensive, studies in this area.